2022
DOI: 10.1177/02841851221128213
|View full text |Cite
|
Sign up to set email alerts
|

Association between quantitative spectral CT parameters, Ki-67 expression, and invasiveness in lung adenocarcinoma manifesting as ground-glass nodules

Abstract: Background Few studies about lung ground-glass nodules (GGNs) have been done using non-enhancement spectral computed tomography (CT) imaging. Purpose To examine the association between spectral CT parameters, Ki-67 expression, and invasiveness in lung adenocarcinoma manifesting as GGNs. Material and Methods Spectral CT parameters were analyzed in 106 patients with lung GGNs. The Ki-67 labeling index (Ki-67 LI) was measured, and patients were divided into low expression and high expression groups according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…It was found that the proliferative activity marker Ki‐67 expression was significantly lower in MIA than in IA. [ 22 ] The low proliferative activity of MIA tumor cells may partly explain why MIA manifests as an indolent tumor. However, we also observed that the malignant cells in MIA featured a basal‐like molecular character.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the proliferative activity marker Ki‐67 expression was significantly lower in MIA than in IA. [ 22 ] The low proliferative activity of MIA tumor cells may partly explain why MIA manifests as an indolent tumor. However, we also observed that the malignant cells in MIA featured a basal‐like molecular character.…”
Section: Discussionmentioning
confidence: 99%